2014
DOI: 10.2169/internalmedicine.53.2918
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Smoking and Responsiveness to Clopidogrel in Non-cardiogenic Ischemic Stroke Patients

Abstract: Objective Clopidogrel is used to prevent the recurrence of non-cardiogenic ischemic stroke, but individual responsiveness to the drug varies. Moreover, it is known that smoking, which is a risk factor for ischemic stroke, affects the drug's pharmacokinetics. The objective of the present study was to investigate a possible relationship between smoking and responsiveness to clopidogrel in non-cardiogenic ischemic stroke patients. Methods The study involved 209 non-cardiogenic ischemic stroke patients who were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
7
2
Order By: Relevance
“…Kang et al [45] and Rath et al [22] showed that smokers who experience ischemic stroke exhibit lower PRU values, which is synonymous with a lower platelet reactivity, compared with nonsmokers. Similarly, Maruyama et al [46] demonstrated that smokers achieve significantly lower platelet reactivity values (128 vs. 167 PRU, p = 0.002) than nonsmokers and, additionally, the incidence of clopidogrel resistance is significantly lower in smokers (12.9% vs. 25.9%; p = 0.033). Zhang et al [47] concluded that the antiplatelet effect of clopidogrel in ischemic stroke patients is much better in smokers and showed a statistical trend for a reduced risk of recurrent vascular events with clopidorel than with aspirin [47].…”
Section: Risk Factors For Vascular Disease Developmentmentioning
confidence: 88%
See 1 more Smart Citation
“…Kang et al [45] and Rath et al [22] showed that smokers who experience ischemic stroke exhibit lower PRU values, which is synonymous with a lower platelet reactivity, compared with nonsmokers. Similarly, Maruyama et al [46] demonstrated that smokers achieve significantly lower platelet reactivity values (128 vs. 167 PRU, p = 0.002) than nonsmokers and, additionally, the incidence of clopidogrel resistance is significantly lower in smokers (12.9% vs. 25.9%; p = 0.033). Zhang et al [47] concluded that the antiplatelet effect of clopidogrel in ischemic stroke patients is much better in smokers and showed a statistical trend for a reduced risk of recurrent vascular events with clopidorel than with aspirin [47].…”
Section: Risk Factors For Vascular Disease Developmentmentioning
confidence: 88%
“…Zhang et al [47] concluded that the antiplatelet effect of clopidogrel in ischemic stroke patients is much better in smokers and showed a statistical trend for a reduced risk of recurrent vascular events with clopidorel than with aspirin [47]. The explanation of the above dependencies is believed to be the activation of the cytochrome P450 complex by nicotine, which may result in a more efficient metabolization of clopidogrel by the liver, leading to increased platelet inhibition [46]. Other risk factors for vascular diseases, such as hypertension, hiperlipidemia, atrial fibrillation, alcohol abuse, and obesity, do not contribute significantly to the modification of the antiplatelet effect of clopidogrel among ischemic stroke subjects.…”
Section: Risk Factors For Vascular Disease Developmentmentioning
confidence: 99%
“…Prior smaller pharmacodynamic studies have demonstrated an influence of smoking on clopidogrel‐induced platelet inhibition . Ueno et al reported a relationship between serum cotinine levels and platelet inhibition in response to clopidogrel .…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking enhances the generation of the active metabolite of clopidogrel by inducing CYP1A2 activity . Several studies suggest that there may be a “smokers’ paradox,” as although smoking has many negative effects on cardiovascular health, smokers have greater platelet inhibition and lower rates of high OTR when compared to non‐smokers on clopidogrel . Consistent with this observation, the CLARITY—TIMI 28 (Clopidogrel as Adjunctive Reperfusion Therapy—Thrombolysis in Myocardial Infarction 28), CHARISMA (Clopidogrel for High Atherothrombotic Risk and Ischemic Stabilization, Management, and Avoidance), and CURRENT‐OASIS 7 (Clopidogrel and Aspirin Optimal Dose Usage to Reduce Recurrent Events—Seventh Organization to Assess Strategies in Ischemic Symptoms) trials all suggested that the clinical benefit of clopidogrel might be greater in smokers compared to non‐smokers .…”
Section: Introductionmentioning
confidence: 92%
“…Cigarette smoking is an inducer of CYP1A2, which can upregulate the CYP1A2 activity, thereby may increase the conversion of clopidogrel into its active metabolite [14] leading to more potent efficacy. Compared with nonsmokers, clopidogrel therapy in current smokers is correlated with strengthened platelet inhibition, decreased aggregation and less occurrence of clopidogrel resistance [15,16]. Moreover, the increased inhibition of platelet aggregation by clopidogrel in smokers diminished after smoking cessation [17], indicating the clopidogrel responsiveness may be enhanced by smoking.…”
Section: Discussionmentioning
confidence: 99%